The quality of internal medicine hospital care during summer holiday season - Jussi Sipilä; Tommi Kauko; Ville Kytö; Teija Stormi; Päivi Rautava (Wiley, 2025)
Rationale, aims and objectives The July/August Phenomenon is a period when the
quality of care in hospitals is thought to decrease due to summer vacation stand-ins and new
staff. The results of studies on the veracity of this claim have been conflicting. This study
investigates the situation in internal medicine.
Methods Registry data of patients treated in internal medicine wards between 1 July 2000
and 30 November 2009 were obtained and analysed.
Results There were no differences in mortality during the July admissions compared with
those in November when adjusting for age, diagnosis, gender and year [for the overall data
risk ratio (RR) = 1.10, 95% confidence interval (CI) 1.00–1.23, P = 0.06; for the university
hospitals RR = 1.10, 95% CI 0.91–1.33, P = 0.34; for the non-university hospitals
RR = 1.10, 95% CI 0.97–1.26, P = 0.13]. The duration of admission (overall mean 4.5,
standard deviation 6.0) was equal between July and November when adjusted for age,
diagnosis, gender and year in all groups (overall data: RR = 1.00, 95% CI 0.99–1.02,
P = 0.83; university hospitals RR = 1.02, 95% CI 0.99–1.04, P = 0.13; non-university
hospitals RR = 1.00, 95% CI 0.98–1.01, P = 0.67).
Conclusions The quality of care in Finnish internal medicine wards in July seems
to equal November. Our results do not support the existence of a July Phenomenon in
Finland.